Dualny model międzyregionalny i jego przydatność w planowaniu - Juja, Tadeusz (Wydział Prawa i Administracji UAM, 1972)
The aim of the article is to discuss the possibility of using an interregional dual programming model in the central planning for regional development. First, a direct two-period interregional model has been presented and then that model has been used for constructing its dual. As a result of solving the dual of an interregional programming model one obtained the following dual variables (accounting prices): regional prices for commodities, transportation services, manpower, valuations on restrictions concerning production increases, old production facilities, national investment quotas, export to and import from particular foreign markets. These accounting prices point to the directions of changes in the free terms of constraints where one could find an improvement to the objective function. Therefore they are of paramount importance to the planner. The article contains a detailed review of factors which determine the regional differentiation of accounting prices and a survey of possibilities how to equalize them in space. In the author's view the only possibility to eliminate regional differences in accounting prices exists with respect to mobile resources, particularly to the labour force.
The Interregional Dual Model and its Application to Planning